Triple helix model in the Czech tertiary education - Sabolová, Veronika (Univerzita Pardubice, 2010)
The article is devoted to the issue of triple helix model and its application in the Czech tertiary education. Introduction describes the crucial provisions of the White Paper on Tertiary Education. Then the triple helix model is described based on the foreign literature search. Particular attention is focused on the importance of the triple helix model in the White Paper on Tertiary Education. Finally, possible subjects of the cooperation between university, industry and government are indicated.
Keywords: triple helix model; Czech tertiary education; white paper on tertiary education